Development of Principal Collaborative-Based Academic Supervision at Madrasah Ibtidaiyah, Rembang Regency - Ashiful Faizin; Ahmad Hariyadi; Gunawan Setiadi; Pratama, Hendri (Studies in Technology and Education, 2024)
This study explores the implementation of collaborative-based academic supervision to improve teacher competency in Madrasah Ibtidaiyah in Rembang Regency. Collaborative-based academic supervision is characterized by partnership-based interactions between supervisors and supervisees. The research employs a research and development (R&D) methodology, combining qualitative and quantitative data analysis techniques. Data collection methods include interviews, observations, documentation, and questionnaires. Expert validators, including education management experts, education practitioners, and language experts, assessed the feasibility of a guidebook for collaborative-based academic supervision. The findings indicate that principals and teachers in three Madrasah Ibtidaiyah in Rembang Regency recognize the need for collaborative-based academic supervision guidelines. The validated guidebook was deemed suitable for use, and teachers affirmed its appropriateness for enhancing supervision practices.